(3GdJfXje GdbGfhfj dJhQjb GdMbhb GdeGdjI (B: s (3OQGSI JMdjdjI ebGQfI Hjf GdbhGfjf GdhVYjI (B/ s - (3HKjfI Ydi fhQ GdOjfs; (3gGfj SQj GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhdJ gPg GdOQGSI fXGe JhQjb GdMbhb GdeGdjI GdBLdI(B: (3HhUag CMO BdjGJ GdJehjd GdeSJMOKI(B: (3h GdPj jNJda Yf BdjGJ GdJehjd GdJbdjOjI GdJj YQagG GdbWGY GdeUQaj(B: (3h Pdc ef NdGd OQGSI bGfhfjI ebGQfI Hjf GdbhGfjf GdhVYjI JYfj HGdJCUjd GdbGfhfj dfXGe GdJhQjb(B. (3h bO GSJgOa GdHMK HGYJHGQg OQGSI bGfhfjI ebGQfI Edi GdJYQja HfXGe GdJhQjb h eagheg(B: (3h CfhGYg(B: (3h JejjRg Yf ZjQg ef GdfXe GdbGfhfjI GdTHjgIs
(3jTJed Ydi edGMbs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B331-359s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdHGOF HGdJhQjbs; (3GdJfXje GdbGfhfj dJhQjb GdMbhb GdeGdjIs; (3GdTQcI PGJ GdZQV GdNGUs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes